Targeting Safety: Hazard Identification and Risk Assessment in the Work of Wood Carving in Tunjungsekar, Malang City, Using the HIRADC Method - Resti Novita Sari; Awanda Putra Pratama; Maharani Rohma Hidayanti; Nadia Rosalinda; Nurmila Kurnia; Shalma Khoirun Nisa'; Anita Sulistyorini (Universitas Negeri Malang, 2024)
The furniture industry in Tunjungsekar Subdistrict has become one of the leading industrial centers in Malang City, successfully boosting the local economy by employing 90 percent of the workforce. However, this industry faces productivity challenges due to an ergonomically unfavorable work environment. Therefore, practical actions and in-depth analysis are needed to improve the work environment issues. This study aims to identify hazards and assess risks associated with the work of wood carving artisans in Tunjungsekar, Malang City, using the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method. Identification was carried out through direct observation and interviews with artisans, followed by analyzing hazards and risks at each stage of work using the HIRADC method with a 5 multiple 5 matrix. This research design uses a descriptive quantitative research design with a cross-sectional approach. The identification and analysis results showed 33 potential hazards that could lead to 59 risks across all work stages. These 59 risks were categorized into low, medium, and high based on the potential hazard level and the extent of exposure. Several control recommendations were proposed based on the risk assessment results, which can be implemented to reduce or eliminate the risks experienced by the wood carving artisans in Tunjungsekar, Malang City.